1981
DOI: 10.1177/000348948109000416
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Tracheal Stenosis

Abstract: Twenty-one cases of congenital tracheal stenosis seen at the Royal Alexandra Hospital for Children 1971 through 1980 were reviewed with regard to the clinical features, associated anomalies, endoscopic findings and radiological evaluation. Congenital tracheal stenosis was usually a serious problem often associated with other major anomalies of the respiratory tract, esophagus, or skeleton. There was no set pattern of presentation. The presenting features included: persistent wheeze or stridor, atypical "respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 7 publications
0
59
0
Order By: Relevance
“…19,37,38 The poor outcomes associated with early attempts at surgical repair led to a general consensus that CTS was not amenable to operative repair; instead, many clinicians employed palliative strategies such as tracheostomy to treat CTS. 26 There are some data to support the implementation of a conservative management strategy in a subset of patients with CTS who have been demonstrated to outgrow their tracheal stenosis by the age of 7 to 9 years. 2 However, it is imperative that careful long-term clinical monitoring is employed, given a significant number of these patients will eventually require surgical intervention to treat worsening symptoms.…”
Section: Therapeutic Approaches and Treatment Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,37,38 The poor outcomes associated with early attempts at surgical repair led to a general consensus that CTS was not amenable to operative repair; instead, many clinicians employed palliative strategies such as tracheostomy to treat CTS. 26 There are some data to support the implementation of a conservative management strategy in a subset of patients with CTS who have been demonstrated to outgrow their tracheal stenosis by the age of 7 to 9 years. 2 However, it is imperative that careful long-term clinical monitoring is employed, given a significant number of these patients will eventually require surgical intervention to treat worsening symptoms.…”
Section: Therapeutic Approaches and Treatment Indicationsmentioning
confidence: 99%
“…In children with unilateral lung agenesis, the trachea continues into the right or left main bronchus, with the contralateral bronchus being either absent or severely hypoplastic. 25 Isolated CTS is present in just 10% to 30% of patients, 13,20,26,27 instead it is frequently associated with other cardiovascular and extrathoracic anomalies. Cardiovascular anomalies occur in up to 70% of patients 13 and include pulmonary artery sling, patent ductus arteriosus, atrial septal defect, ventricular septal defect, atrioventricular septal defect, double aortic arch, partial anomalous pulmonary venous connection, Tetralogy of Fallot, complete transposition of the great arteries, and tricuspid atresia.…”
mentioning
confidence: 99%
“…In his initial review, Wolman [14] states that the "prognosis is not hopeless...; as the infant grows up, the trachea grows too," the evidence being based on adult autopsy studies. In their review of 21 cases from 1971 to 1980 in Australia, Benjamin et al [16] found that 12/21 children survived, of whom only two required surgical intervention (one pneumonectomy, one tracheostomy), the remainder receiving only conservative management. The authors noted that some children "live reasonably happily with their disease -the stenosis apparently 'growing' with the child.…”
Section: Discussionmentioning
confidence: 99%
“…The trachea is therefore rigid and non-distensible (11). This may occur diffusely throughout the trachea or in part of the trachea.…”
Section: Congenital Tracheal Stenosismentioning
confidence: 99%